Innovare per migliorarsi in un periodo di grandi rischi e difficoltà - Pettinari, Claudio (Antonianum, 2025)
Claudio Pettinari here reviews his six years as the Rector of the University of Camerino, a period marked by dramatic events such as the 2016 earthquake and the 2020 pandemic. Through a narrative that is at once personal and institutional, the Author describes how the University rose to the challenges with resilience, focusing on innovation, digitalization, and, above all, on renewing institutional relationships and cooperation with the local community. Central to this account is the idea that true innovation cannot exist without connections: connections between persons, institutions, kinds of knowledge, and local communities. In this manner, the university is endowed with social agency and becomes capable of bringing about social cohesion and development, realizing the value of communications, shared research, and strategic vision.